الاحت ا رق الوظیفي لدى مربي ذوي الاحتیاجات الخاصة - د ا رسة میدانیة بالمؤسسات المختصة بالاغواط و الجلفة - - bourzegue, kamel (Finance and Business Economies Review, 2018)
Today's This study aims to investigate the level of the occupational combustion among people with special needs educators, identify this level in terms of experience and know the gender differences. The study was based on the Maslash scale of psychological combustion. When the results were applied and analyzed, the study revealed the existence of a moderate level to the occupational combustion among people with special needs educators and the absence of differences with statistical significance due to both gender and experience variables .